2007
DOI: 10.1016/j.neulet.2007.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane depression of spinal nociceptive processing and minimum alveolar anesthetic concentration are not attenuated in mice expressing isoflurane resistant γ-aminobutyric acid type-A receptors

Abstract: Anesthetics produce immobility and depress spinal nociceptive processing, but the exact sites and mechanisms of anesthetic action are unknown. The gamma-aminobutyric acid type-A (GABA A ) receptor is thought to be important to anesthetic action. We studied knockin mice that had mutations in the alpha1 subunit of the GABA A receptor that imparts resistance to isoflurane in in vitro systems. We determined the isoflurane minimum alveolar concentration (MAC) that produces immobility in 50% of subjects and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…These results are consistent with previous pharmacologic studies that have demonstrated that GABA A -Rs in the spinal cord are not key mediators of anesthetic-induced immobility 29,30…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous pharmacologic studies that have demonstrated that GABA A -Rs in the spinal cord are not key mediators of anesthetic-induced immobility 29,30…”
Section: Discussionsupporting
confidence: 93%
“…Evoked responses of dorsal horn neurons to noxious stimuli have reportedly been depressed by periMAC dose increases of halothane and isoflurane 811,19. However, further studies failed to confirm isoflurane-induced depression of dorsal horn neurons and suggest periMAC increases of isoflurane dose may facilitate neuronal response to noxious stimulation 10,11.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, mice expressing an isoflurane-resistant knock-in α1 GABA A receptor subunit did not change either MAC or the suppression of neuronal responses to noxious stimulation. 10 Yet sensitivity to other GABAergic sedatives, including methohexital 11 and midazolam, 12 also increases with ageing. Perhaps ageing-related changes in GABA A receptor subunit expression or other, compensatory modifications that occur with ageing could explain the increased sensitivity to anaesthetics in older animals.…”
mentioning
confidence: 99%